Transforming a Didactic Lecture into a Student-Centered Active Learning Exercise-Teaching Equine Diarrhea to Fourth-Year Veterinary Students - Stuart J. G. Gordon; Charlotte F. Bolwell; Jessica L. Raney; Nick Zepke (MDPI AG, 2022)
Problem-solving abilities, creative and critical thinking, communication skills, and teamwork are now recognized as fundamental determinants of professional success, especially in vocational professions, such as veterinary science. Tertiary education is now obliged to provide opportunities for students to become proficient in these qualities. With this in mind, the principal author, an equine science senior lecturer, attempted to increase student engagement by developing a new active learning, student-centered one-hour teaching episode on 'equine diarrhea', to replace the traditional didactic lecture format. The aim of the study, therefore, was to share the principal author's journey in the development and implementation of this active learning episode and to explain why it represents a simple but effective method of promoting student engagement. In addition, the adaptation of this method into an online teaching and learning format is briefly discussed. The effectiveness of this active learning method is also explored by comparing it with the traditional didactic method of delivery. Students in the active learning class reported that the learning activity had enhanced their skills in clinical reasoning, problem-solving, and communication. They also described themselves as active participants in the learning process. Students in the traditional didactic class reported that they were satisfied with the time allocated to the lecture, felt that the lecture was well organized and managed, and subsequently felt adequately prepared to answer conventional examination questions relating to equine diarrhea. Other issues, such as student resistance to changes in teaching formats, the effectiveness of group work or teamwork, levels of student confidence within an active learning environment, and the importance of high-quality facilitation during active learning activities, are also discussed in this paper. Although the active learning method described is not novel, the authors hope that fellow educators, across any tertiary discipline, might find that the method described represents a quick and simple method of transforming a single didactic lecture into an enjoyable and engaging learning activity.